Rekognisi Ḥadīṡ Iftirāq Dalam Ruang Multikultural - Miski Miski (Institut Agama Islam Negeri (IAIN) Curup, 2023)
The purpose of this research is to analyze two main things, namely how the iftiraq hadith is used as a tool to legitimize the existence of other groups, and how to actualize this hadith in multicultural life. This research also uses a fiqh al-ḥadīṡ approach with a descriptive-hermeneutical analysis model. This research has shown two things. First, the concepts of